The European Union and the member states: which level of government should do what?: An empirical analysis of Europeans' preferences - Floriana Cerniglia; Laura Pagani (Center for Economic Studies and ifo Institute (CESifo), 2007)
In this paper we empirically study the preferences of European citizens concerning the allocation of powers between EU and the Member States using Eurobarometer data from 1995 to 2003. Descriptive analysis highlights a ranking of countries according to their level of Europeanism, and a quite clear pattern of preferences relative to the allocation of competences for specific policy domains. With econometric analysis, first we regress a measure of Europeanism on a number of individual characteristics and, second, we select some policy domains and investigate the determinants of preferences for centralisation of competences at the EU level. Also econometric analysis reveals interesting patterns regarding EU citizens' preferences for allocation of powers.
Keywords: H11; H77; 330; Föderalismus; Zentralstaat; Präferenztheorie; Meinung; Europäische Integration; EU-Staaten